Taxonomy of trends’ types: a concise proposal - Queiroz Campos, Amanda (2020)
The word trend was extensively used, and forcedly associated with products and services as an argument, qualification, or legitimation. In addition, one sees the application of a range of various taxonomies within the semantic scope of the word, which compromises their understanding and study. The objective of this study was to reduce the complexity of the concept and to standardize its terminologies. The nature of the research was qualitative and analytical. The methodology approach comprised bibliographical and comparative research, contrasting data from different authors regarding the taxonomies applied to characterize different typologies of trends. Applying axial coding (Grounded Theory), the quantity of terms was reduced to two: macro trends and micro trends. Macro trends correspond to broad sociocultural tendencies that have long duration and high impact. Micro trends are less durable and impactful, reaching only a few market segments by presenting guidelines for products and services.